Investigation of Air oxidation and hot corrosion behavior of Boiler grade material Austenitic stainless steel AISI 347. (2020) - Muthu, S.M.; Venkateshkannan, M.; Gupta, Shubham; Surya Prakash, K.; Arivarasu, M.; Arivazhagan, N.
Abstract: The air oxidation and hot corrosion behavior of the austenitic stainless steel AISI 347 is investigated in air and K2SO4-60%NaCl environment at 700°C for 10cycles. This material is used in nuclear power plant and waste heat incinerators due to its excellent mechanical properties at high operating temperature and uniform corrosion resistance. The oxidation and corrosion kinetics of the steels are determined by thermo-gravimetric technique. The steel AISI 347 after oxidation and hot corrosion, surface morphology and chemical compositions are characterized using scanning electron microscope with energy dispersive spectroscopy. The phases of the steels are analyzed using X-ray diffraction method. The cross-sectional analysis is carried out to ensure the oxide scale thickness and corrosion attack. From the results, higher weight gain is observed in the hot corroded steel. Hot corroded steel is severely suffered than oxidized steel particularly more oxide scale spilling is observed in the hot corroded steel